A potential role of p75NTR in the regulation of circadian rhythm and incremental growth lines during tooth development - Yuan, Hongyan; Xie, Bo; Yu, Xia; Lin, Cheng; Li, Meng; Zhang, Yixin; Zou, Xuqiang; Lu, Mingjie; Zhao, Manzhu; Wen, Xiujie (Frontiers in Physiology, 2022)
Objective: Tooth morphogenesis and the formation of hard tissues have been reported to be closely related to circadian rhythms. This study investigates the spatiotemporal expression and relationship of p75NTR with core clock genes, mineralization-related or odontogenesis-related genes, and aims to derive the potential role of p75NTR in regulating circadian rhythm and incrementality growth line formation during tooth development. Materials and methods: The dynamic morphology of the rat dental germ was observed at seven stages (E14.5 d, E16.5 d, E18.5 d, P.N. 4 d, P.N. 7 d, P.N. 10 d, and P.N. 15 d). Next, the expressions of p75NTR and other target factors were traced. The ectomesenchymal stem cells (EMSCs) were isolated from the E18.5 d rat dental germs and synchronized using 50% of fetal bovine serum. Then, they were cultured in light/light (L.L.), dark/dark (D.D.), and light/dark (L.D.) conditions for 48 h. The total RNA was collected every four hours, and the circadian rhythm dynamics of target factors were observed. To reveal the mechanism further, p75NTR was down-regulated in p75NTRExIII-/- mice and up-regulated in immortalized mouse dental apical papilla progenitor cells. The change tendencies of other target factors were also detected. Results: The clock genes Bmal1, Clock, Per1, and Per2 were all expressed in tooth germs before the formation of dental hard tissues and demonstrated a regular oscillating expression pattern in EMSCs from dental germs. Their expression was affected by the L.D. stimulus, and most of them were promoted by D.D. conditions. p75NTR presented a similar expression pattern and a positive or negative relationship with most clock genes, mineralization-related and odontogenesis-related factors, such as brain and muscle ARNT-like protein-1 (Bmal1), runt-related transcription factor 2 (Runx2), alkaline phosphatase (ALP), MSH-like 1 (MSX1), and dentin matrix acidic phosphoprotein 1 (Dmp1). Moreover, the arrangement, morphology, and boundary in pre-odontoblast/pre-ameloblast layers were disordered in the p75NTRExIII-/- mice. Conclusion: Circadian rhythm was found to affect tooth development. p75NTR might play a crucial role in regulating clock genes in the mineralization and formation of the dental hard tissues. p75NTR is actively involved in the odontoblast-ameloblast junction and cell polarity establishment during tooth morphogenesis.